3(3x+4)+63=13x+9-4x+66

Simple and best practice solution for 3(3x+4)+63=13x+9-4x+66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+4)+63=13x+9-4x+66 equation:


Simplifying
3(3x + 4) + 63 = 13x + 9 + -4x + 66

Reorder the terms:
3(4 + 3x) + 63 = 13x + 9 + -4x + 66
(4 * 3 + 3x * 3) + 63 = 13x + 9 + -4x + 66
(12 + 9x) + 63 = 13x + 9 + -4x + 66

Reorder the terms:
12 + 63 + 9x = 13x + 9 + -4x + 66

Combine like terms: 12 + 63 = 75
75 + 9x = 13x + 9 + -4x + 66

Reorder the terms:
75 + 9x = 9 + 66 + 13x + -4x

Combine like terms: 9 + 66 = 75
75 + 9x = 75 + 13x + -4x

Combine like terms: 13x + -4x = 9x
75 + 9x = 75 + 9x

Add '-75' to each side of the equation.
75 + -75 + 9x = 75 + -75 + 9x

Combine like terms: 75 + -75 = 0
0 + 9x = 75 + -75 + 9x
9x = 75 + -75 + 9x

Combine like terms: 75 + -75 = 0
9x = 0 + 9x
9x = 9x

Add '-9x' to each side of the equation.
9x + -9x = 9x + -9x

Combine like terms: 9x + -9x = 0
0 = 9x + -9x

Combine like terms: 9x + -9x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x-4=5x+4 | | 3(2x+5)-2x=4(x+3)+3 | | -(-1.3-7p)=3.3+6p | | 2-2y=-22+y | | Blank+blank=936 | | -8x-3=-9x+4 | | x+2(x+4)=66 | | 8x+2x-17+10-5x+20=100 | | 3xy-5a=9b | | b-9+7b=24 | | k-6+12k=7-8k+9-k | | 2(x+5)=2(x-5) | | -8n+(1+5n)=-6n | | K+0.6=3.84 | | -x-3=3x+33 | | (8m-8n)(4m-7n)= | | 8x+7x-88=110-7x | | -3x-(-5)+2x=-x-4 | | 1+5x-40=1x-5 | | x+x+4=36 | | -10+x+4-4-5=7x-5 | | 6x+2(7x-4)=92 | | x+2y=29 | | -3x+8=18+4x | | x+2x=62 | | x-3(x-4)+2=14-3(5x+6) | | 3*n-8=2*n+15 | | 4(6x+3x)=12 | | 60k+60k=50k+100 | | x+x+2=62 | | -9+2.5y-.7y+1+6.4y= | | 2.4x=4x-88 |

Equations solver categories